Association Between Maternal Myopia and Myopia in Children Aged 10-12 Years in Karanggondang, Indonesia: A Cross-Sectional Study - Nabila Dwi Desi Puspita; Herry Susanto; Indra Tri Astuti; Loan Thi Dang (Viva Medika, 2025)
Myopia is the most common refractive error among school-aged children and a growing public health concern, particularly in developing countries. Although parental myopia is widely recognized as a genetic risk factor, evidence from Indonesia, especially among children aged 10 to 12 years, remains limited and inconsistent. By focusing on maternal myopia as a single and practical familial indicator in school-based settings, this study also considers a null association as a meaningful context-specific finding. This observational analytic study employed a cross-sectional design and was conducted from August to October 2025 in three public elementary schools in Karanggondang, Indonesia. A total of 88 child-mother pairs were recruited using purposive sampling. Visual acuity in both children and mothers was assessed using a Snellen chart without cycloplegic refraction. Refractive status was classified dichotomously as myopia or non-myopia. Data were analyzed using descriptive statistics and Chi-square tests with Yates’ continuity correction, and associations were expressed as odds ratios with 95 percent confidence intervals. The prevalence of myopia was 20.5 percent among children and 59.1 percent among mothers. Childhood myopia was slightly more frequent among children of myopic mothers at 12.5 percent compared with 8.0 percent among those of non-myopic mothers. However, no statistically significant association was found between maternal myopia and childhood myopia, with a p value of 1.000. The estimated odds ratio was 1.12 with a 95 percent confidence interval of 0.385 to 3.209. Maternal myopia was not a significant independent predictor of myopia in children aged 10 to 12 years in this population. This context-specific null finding suggests that maternal myopia alone may have limited explanatory value. Preventive strategies should prioritize modifiable lifestyle factors alongside routine vision screening, and future studies should incorporate cycloplegic refraction and broader familial and environmental measures